2014
DOI: 10.1002/2013jg002527
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long-term water table manipulations on dissolved organic carbon dynamics in a poor fen peatland

Abstract: Dissolved organic carbon (DOC) production, consumption, and quality displayed differences after long-term (~55 years) hydrological alterations in a poor fen peatland in northern Michigan. The construction of an earthen levee resulted in areas of a raised and lowered water table (WT) relative to an unaltered intermediate WT site. The lowered WT site had greater peat aeration and larger seasonal vertical WT fluctuations that likely elevated peat decomposition and subsidence with subsequent increases in bulk dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 118 publications
3
33
0
1
Order By: Relevance
“…In addition, the difference in [DOC] dynamics is also reflected in DOM quality inferred from its fluorescence properties, with a greater increase in low molecular weight compounds (component M) and fewer aromatic high molecular 5 weight compounds (component C) in the rewetted location during the dry season compared to the control area. These findings are in agreement with the studies by Höll et al (2009), Hribljan et al (2014 and Strack et al (2015) who observed that wetter sites would result in a pore water with smaller and fewer aromatic dissolved organic molecules (likely sourced from inputs of fresh litter from growing vegetation) than the sites with a lower water table.…”
Section: Doc Concentrations and Control Factorssupporting
confidence: 92%
See 3 more Smart Citations
“…In addition, the difference in [DOC] dynamics is also reflected in DOM quality inferred from its fluorescence properties, with a greater increase in low molecular weight compounds (component M) and fewer aromatic high molecular 5 weight compounds (component C) in the rewetted location during the dry season compared to the control area. These findings are in agreement with the studies by Höll et al (2009), Hribljan et al (2014 and Strack et al (2015) who observed that wetter sites would result in a pore water with smaller and fewer aromatic dissolved organic molecules (likely sourced from inputs of fresh litter from growing vegetation) than the sites with a lower water table.…”
Section: Doc Concentrations and Control Factorssupporting
confidence: 92%
“…In addition, anaerobic conditions in the rewetted site would lead to less efficient decomposition of organic matter, increasing the production of water-soluble intermediate metabolites (Kalbitz et al, 2000;Strack et al, 2008). An increase in [DOC] in the rewetted location can also be explained by an increase in the photic zone, potentially supporting algae photosynthate production enhancing DOC release into the water column, as suggested by Hribljan et al (2014). However the latter hypothesis is the 25 least probable in our case since no ponding water is observed in summer in the study area.…”
Section: Doc Concentrations and Control Factorssupporting
confidence: 62%
See 2 more Smart Citations
“…It is likely that changes in DOM character exert varying interference effects on spectrophotometric determination of Fe species in different peatland ecosystems, such as in bogs vs. fens. For example, changes in water residence time and connectivity with groundwater in different peatlands influence DOM character (Hribljan et al, 2014), which likely interacts with changes in alkalinity in governing Fe speciation (Boomer and Bedford, 2008). Therefore, to accurately appreciate the role Fe plays in anaerobic metabolism in bogs and fens it is important to critically evaluate spectrophotometric determination of Fe in the challenging matrix of peat pore water and to identify conditions where spectrophotometric approaches are not suitable.…”
mentioning
confidence: 99%